The impact of early childhood parental loss on children's self concept, peer relations, emotional and behavioral problems, and school achievement - Özgül, Doğa. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1995., 1995)
This causal-comparative research examined the effects of early childhood loss on self-concept, peer popularity, externalizing and internalizing problems and school achievement of children. Early childhood loss was defined as the death of either parent before the child is six years old. Participants of this study were elementary school students from grades 3 to 5. They were 68 individuals (34 boys, 34 girls). Half of them had experienced early parental death while the remaining half came from intact families. Piers-Harris Children's Self Concept Scale, a sociometric rating, teacher ratings of externalizing and internalizing problems, standardized cumulative grade point averages and a structured interview were used in the study. In addition to effects ofloss, effects of gender were investigated. Thus, two-way analysis of variance were utilized in comparison ofthe groups. Results indicated that the loss group had lower self-concept, peer popularity, school achievement and higher externalizing behaviours than the intact group. Effects of loss were equally detrimental for both gender. Since the researcher found no study on direct effects of early loss on Turkish children, this study is an important step indicating the needs of bereaved children.
Keywords: Loss(Psychology) in children.